The Care Theory of Dignity Amid Personal Data Digitalization - Leidner, Dorothy E.; Tona, Olgerta (MIS Quarterly, 2021)
With the rapidly evolving permeation of digital technologies into everyday human life, we are witnessing an era of personal data digitalization. Personal data digitalization refers to the sociotechnical encounters associated with the digitization of personal data for use in digital technologies. Personal data digitalization is being applied to central attributes of human life—health, cognition, and emotion—with the purported aim of helping individuals live longer, healthier lives endowed with the requisite cognition and emotion for responding to life situations and other people in a manner that enables human flourishing. A concern taking hold in manifold fields ranging from IT, bioethics, and law, to philosophy and religion is that as personal data digitalization permeates ever more areas of human existence, humans risk becoming artifacts of technology production. This concern brings to center stage the very notion of what it means to be human, a notion encapsulated in the term human dignity, which broadly refers to the recognition that human beings possess intrinsic value and, as such, are endowed with certain rights and should be treated with respect. In this paper, we identify, describe, and transform what we know about personal data digitalization into a higher order theoretical structure around the concept of human dignity. The result of our analysis is the CARE (claims, affronts, response, equilibrium) theory of dignity amid personal data digitalization, a theory that explains the relationship of personal data digitalization to human dignity. Building upon the CARE theory as a foundation, researchers in a variety of IS research streams could develop mid-range theories for empirical testing or could use the CARE theory as an overarching lens for interpreting emerging IS phenomena. Practitioners and government agencies can also use the CARE theory to understand the opportunities and risks of personal data digitalization and to develop policies and systems that respect the dignity of employees and citizens.